Spatial and temporal distribution of the minke whale, Balaenoptera acutorostrata (Lacepede, 1804), in the southern northeast Atlantic Ocean and the Mediterranean Sea, with reference to stock identity - Van Waerebeek, Koen; Andre Vely, Michel; Sequeira, Marina; Martín, Vidal; Robineau, Daniel; Collet, Anne; Papastavrou, Vassili; Ndiaye, Edouard (J. Cetacean Res. Manage., 1999)
New strandings. bycatch and sightings data for minke whales in the northeast Atlantic Ocean south of Cape Finisterre (Galicia) and the Mediterranean Sea were combined with earlier authenticated records, in order to re-assess spatial and temporal distribution, and provide clues to breeding areas and stock identity. The southern range of IWC-defined Nonheastem Atlantic and Central North Atlantic stocks with no explicit. but a de Jam, boundary of the Equator, was explored in particular. Senegal (6 records). Mauritania (1) and Western Sahara/Southern Morocco (3) are new West African Range States for the North Atlantic minke whale. Morocco and The Gambia are likely Range States. Specimens stranded or captured in Senegal and Mauritania were either calves (a-6) or neonate (a= IL a strong indication for a near-by calving ground. Juveniles and calves (median SL:418cm, a =6) commonly occur off the Canary Islands, without apparent seasonality. Two strandings, one of which was a neonate (in February), were documented in the Azores. Evidence of minke whales is lacking for Madeira and the Cape Verde Islands. The temporal distribution of 33 records from the western coasts of the Iberian Peninsula in the period 1905-1998 included all seasons, but 76% were registered in spring and summer (March-August). The majority of animals were juveniles (mean SL:537.5cm. a-26); none were neonates. Minke whales were encountered in low numbers in the western and central Mediterranean Sea mostly front March to November. although documented strandings in December and February argue for a year-round presence. The Ligurian and Tyrrhenian Seas and the Gulf of Lion are concentration areas, presumably (cf. fin whales) linked to the abundance of euphausiids. Small calves (SL:300-360cm) suggest that at least some females give birth in the Mediterranean. An unusual stranding in the eastern Black Sea (Georgia) may be related to migration of schooling fish. The southernmost specimen known from the North Atlantic is a calf captured near Hann (14741’N, 17°27’W). Senegal. in May. Southernmost sightings include: (a) inshore: a foraging individual at Garnet’s Bay (24°5I’N, 15°05’W) in November. (b) offshore: three minke whales at 10°40’N. 22°00’W in December. While small, the sample from %Vest Africa does not seem to support a restricted, seasonal presence. Most likely, these individuals constitute the offspring and juveniles from the Northeastern Atlantic and/or Central North Atlantic populations, but an unrecognised local population cannot be discounted. Preliminary cladistic analysis of the mtDNA control region of one Senegal minks whale yielded equivocal results depending on the fragment sequenced. Field research in the region should be continued to provide the necessary samples to resolve the question of stock identity.